Adjunctive Host-Directed Therapy With Statins Improves Tuberculosis-Related Outcomes in Mice. (12th October 2019) - Dutta, Noton K; Bruiners, Natalie; Zimmerman, Matthew D; Tan, Shumin; Dartois, Véronique; Gennaro, Maria L; Karakousis, Petros C
Abstract: Background: Tuberculosis (TB) treatment is lengthy and complicated and patients often develop chronic lung disease. Recent attention has focused on host-directed therapies aimed at optimizing immune responses to Mycobacterium tuberculosis (Mtb), as adjunctive treatment given with antitubercular drugs. In addition to their cholesterol-lowering properties, 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) have broad anti-inflammatory and immunomodulatory activities. Methods: In the current study, we screened 8 commercially available statins for cytotoxic effect, anti-TB activity, synergy with first-line drugs in macrophages, pharmacokinetics and adjunctive bactericidal activity, and, in 2 different mouse models, as adjunctive therapy to first-line TB drugs. Results: Pravastatin showed the least toxicity in THP-1 and Vero cells. At nontoxic doses, atorvastatin and mevastatin were unable to inhibit Mtb growth in THP-1 cells. Simvastatin, fluvastatin, and pravastatin showed the most favorable therapeutic index and enhanced the antitubercular activity of the first-line drugs isoniazid, rifampin, and pyrazinamide in THP-1 cells. Pravastatin modulated phagosomal maturation characteristics in macrophages, phenocopying macrophage activation, and exhibited potent adjunctive activity in the standard mouse model of TB chemotherapy and in a mouse model of human-like necrotic TB lung granulomas. Conclusions: These data provide compelling evidence for clinical evaluation of pravastatin as adjunctive, host-directed therapy for TB.